Interannual perturbations of the Martian surface heat flow by atmospheric dust opacity variations. Issue 10 (25th October 2016) - Plesa, A.‐C.; Grott, M.; Lemmon, M. T.; Müller, N.; Piqueux, S.; Siegler, M. A.; Smrekar, S. E.; Spohn, T.
Abstract: The InSight (Interior Exploration using Seismic Investigations, Geodesy and Heat Transport) mission will perform the first Martian in situ heat flow measurement by deploying the Heat Flow and Physical Properties Package (HP 3 ) onto the Martian surface. In order to estimate the heat flow coming from the planetary interior, HP 3 will measure the local subsurface thermal gradient as well as the local thermal conductivity to a depth of up to 5 m. From these measurements, local heat flow can be determined, but this will in general differ from the heat flow emanating from the planetary interior due to atmosphere‐induced perturbations. Here we quantify heat flow perturbation induced by dust loading of the Martian atmosphere using dust opacity data obtained by the Mars Exploration Rover Opportunity. Dust opacity data span the time period between Mars year (MY) 27 and MY 32, thus incorporating the global dust storm event of MY 28 as a signal. We consider two end‐member cases for the regolith thermal conductivity and find that the background planetary heat flow is superposed by atmosphere‐induced perturbations of less than 1.5 mW m −2 at depths below 2 m if regolith thermal conductivity is low and around 0.025 W m −1 K −1 on average. If thermal conductivity is high and around 0.05 W m −1 K −1 on average, perturbations are less than 2.5 mW m −2 at depths below 3 m. Overall, the influence of interannual variability on subsurface heat flow is found to be moderate following a global dust storm. Considerably smaller perturbations are introduced by regional dust storms, which are of shorter duration and smaller magnitude. Key Points: We use a 5 Mars years time series of the Martian atmospheric dust opacity data to quantify the magnitude of the heat flow perturbations Numerical simulations show minor and moderate pertubation of the heat flow caused by local and global dust storm, respectively The heat pulse introduced by global dust storms travels up to a depth of 3 m and can only be observed in the Mars year following the storm